Extracellular Vesicles Derived From Talaromyces marneffei Yeasts Mediate Inflammatory Response in Macrophage Cells by Bioactive Protein Components - Yang, Biao; Wang, Jingyu; Jiang, Hongye; Lin, Huixian; Ou, Zihao; Ullah, Amir; Hua, Yuneng; Chen, Juanjiang; Lin, Xiaomin; Hu, Xiumei; Zheng, Lei; Wang, Qian (Frontiers in Microbiology, 2021)
Extracellular vesicles (EVs), loaded with proteins, nucleic acids, membrane lipids and other virulence factors, could participate in pathogenic processes in some fungi such as Cryptococcus neoformans and Candida albicans. However, the specific characteristics of EVs derived from Talaromyces marneffei (TM) still have not been figured out yet. In the present study, it has been observed that TM-derived EVs were a heterogeneous group of nanosized membrane vesicles (30-300nm) under nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). The DiI-labeled EVs could be taken up by RAW 264.7 macrophage cells. Incubation of EVs with macrophages would result in increased expression levels of reactive oxygen species (ROS), nitric oxide (NO) and some inflammatory factors including IL-1β, IL-6, IL-10 and TNF-α. Furthermore, the expression of costimulatory molecules (CD80, CD86, MHC-II) were also increased in macrophages stimulated with EVs. The level of inflammatory factors secreted by macrophages showed a significant decrease when EVs were hydrolyzed by protease, while that of DNA and RNA hydrolase treatment remained unchanged. Subsequently, some virulence factors in EVs including heat shock protein, MP1p and peroxidase were determined by LC-MS/MS. Taken together, our results indicated that the TM-derived EVs could mediate inflammatory response and its protein would play a key role in regulating the function of RAW 264.7 macrophage cells